ACCOUNTING INFORMATION SYSTEMS INFLUENCE BUSINESS DECISION QUALITY: FINANCIAL LITERACY AND GOVERNANCE MODERATION - Wahyu Nugroho; Elvin Bastian; Roza Mulyadi (Jurnal Media Ekonomi (JURMEK), 2026)
Research Gap: Prior studies largely examine the direct effects of accounting information systems on decisions in private organizations, leaving unclear whether users' financial capability and governance arrangements jointly determine the decision value of accounting information in public-community enterprises. Purpose: This study examines whether accounting information systems (AIS) and management accounting information systems (MAIS) improve business decision quality and whether financial literacy and governance strengthen those relationships in jointly owned village enterprises. Research Methodology: An associative quantitative survey was conducted among managers of 26 active BUM Desa Bersama-UPK LKD units in Serang Regency, Indonesia. Of 145 questionnaires distributed, 109 usable responses were obtained (75.17%). Reflective constructs were measured using five-point Likert scales and analyzed with PLS-SEM in SmartPLS 4.1.1.8. Results: AIS and MAIS positively affected business decision quality (beta = 0.258 and 0.208; p < 0.001). Financial literacy strengthened the AIS and MAIS effects (beta = 0.291 and 0.340; p < 0.001), while governance also strengthened both effects (beta = 0.327 and 0.335; p < 0.001). The model explained 81.4% of decision-quality variance, had acceptable fit (SRMR = 0.073), and showed positive global predictive relevance (Q2 = 0.814). Conclusions: Accounting information improves decisions not merely because it is available, but because financially literate managers can interpret it and governance mechanisms require transparent, accountable use. Limitations: The cross-sectional, self-reported design and single-regency setting limit causal and geographic generalization; the Q2 statistic is an in-sample global predictive-relevance index rather than an out-of-sample PLSpredict result. Contributions: The novelty lies in modeling financial literacy as an interpretive capability and governance as an agency-control mechanism simultaneously. The findings extend Agency Theory by showing that information systems reduce agency problems only when agents possess the capability and incentives to use evidence responsibly. Practically, BUM Desa Bersama should combine standardized AIS/MAIS reports with financial-literacy development, documented decision protocols, and governance review.